The Influence of Content Marketing and Product Reviews on Customer Satisfaction on Social Media Mediated by Purchase Decisions for Luxcrime Products in Palu City - Aulia, Nurul; Sutomo, Maskuri; Santi, Ira Nuriya; Auriza, Mohammad Zeylo (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of content marketing and product reviews on customer satisfaction, with purchase decisions as a mediating variable, for Luxcrime products in Palu City. A quantitative method was used by distributing online questionnaires to 100 respondents. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results indicate that content marketing and product reviews significantly affect purchase decisions and customer satisfaction. Purchase decisions also mediate the relationship between these variables and customer satisfaction. These findings have implications for cosmetic industry practitioners in optimizing effective digital marketing strategies through social media.